The role of IL-17 in psoriasis. (February 2015) - Malakouti, Mona; Brown, Gabrielle Elena; Wang, Eva; Koo, John; Levin, Ethan C.
Abstract Background: Psoriasis is a chronic skin condition traditionally believed to involve the Th1 pathway. Recently, the IL-23/Th17/IL-17 pathway has been highlighted in the pathogenesis of psoriasis and other autoimmune inflammatory conditions. From a clinician's perspective, we sought to review the basic science data relevant to IL-17's role in psoriasis pathogenesis. Methods: We performed a Pubmed and Web of Knowledge search for English articles starting from 1990 that discussed the Th17 pathway. Search terms such as "IL-17" and "psoriasis" were utilized. Results: The IL-17 pathway is regulated by IL-23, a cytokine that is vital for the expansion and maintenance of the Th17 cell population. Th17 derived cytokines (IL-17A, IL-17F, IL-17A/F and IL-22) were elevated in both psoriasis-like murine models and human psoriatic lesional biopsies. Ixekizumab (anti-IL-17A) treatment of psoriasis was found to normalize levels of IL-17 downstream gene products. Conclusion: Both preclinical and clinical studies support the central role of IL-17 in the pathogenesis of psoriasis.